2011
DOI: 10.1080/01496395.2010.551394
|View full text |Cite
|
Sign up to set email alerts
|

Removal Characteristics of Cd(II), Cu(II), Pb(II), and Zn(II) by Natural Mongolian Zeolite through Batch and Column Experiments

Abstract: The removal characteristics of Cd(II), Cu(II), Pb(II), and Zn(II) from model aqueous solutions by 5 natural Mongolian zeolites were investigated. The adsorption of metals on zeolites reached a plateau value within 6 h. The adsorption kinetic data were fitted with adsorption kinetic models. The equilibrium adsorption capacity of the zeolites was measured and fitted using Langmuir and Freundlich isotherm models. The order of adsorption capacity of zeolite was Pb(II) > Zn(II) > Cu(II) > Cd(II). The maximum adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…These results indicated that the ZIF‐67 integrated composite membrane had a good adsorption capacity, making it suitable for removing heavy metal ions. The performance of this composite membrane was compared with other adsorbents reported in other literatures, as shown in Table 2 , the as‐prepared pearl‐necklace‐like composite membranes showed a competitive adsorption capacity with respect to other adsorbents. Furthermore, the adsorption of other heavy metal ions by sample ZIF/CA‐24 was explored (Figure S4, Supporting Information), and it was noted that the composite membrane also effectively removed other heavy metal ions other than Cu(II) and Cr(VI).…”
Section: Resultsmentioning
confidence: 91%
“…These results indicated that the ZIF‐67 integrated composite membrane had a good adsorption capacity, making it suitable for removing heavy metal ions. The performance of this composite membrane was compared with other adsorbents reported in other literatures, as shown in Table 2 , the as‐prepared pearl‐necklace‐like composite membranes showed a competitive adsorption capacity with respect to other adsorbents. Furthermore, the adsorption of other heavy metal ions by sample ZIF/CA‐24 was explored (Figure S4, Supporting Information), and it was noted that the composite membrane also effectively removed other heavy metal ions other than Cu(II) and Cr(VI).…”
Section: Resultsmentioning
confidence: 91%
“…transform infrared (FTIR) results revealed that the Ca 2+ ions in this Ca-MOF are capable of being exchanged by Cu 2+ almost quantitatively in seconds in aqueous solution. This MOF showed a maximum Cu 2+ sorption capacity of ≈68 mg g −1 at pH = 7, which is higher than those of activated carbons, [60] natural zeolite, [61] and several organic resins [62] (13-60 mg g −1 ). The second-order rate constant k 2 of Ca-MOF is as high as 0.032 g mg −1 min −1 , obtained by exchange kinetics experiment.…”
Section: Capture Of Metal Ions and Other Moleculesmentioning
confidence: 97%
“…There are some studies about removal of zinc and cadmium in a multiple ionic system from wastewaters and solutions by using natural zeolite [16,[21][22][23][24][25][26]. For example, Wingenfelder et al [21] investigated the removal of Fe, Pb, Cd, and Zn from synthetic mine waters by a natural zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not also investigate the kinetic model for this sorption. Furthermore, Batjargal et al [23] investigated the natural zeolite adsorption capacity of Cd(II), Cu(II), Pb(II), and Zn(II) from aqueous solutions that was measured and fitted using Langmuir and Freundlich isotherm models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation